Effect of high levels of human chorionic gonadotropin and estradiol on the severity of hyperemesis gravidarum - Tan, P.C.; Tan, N.C.; Omar, S.Z. (2009)
Background: Serum human chorionic gonadotropin (hCG) and estradiol levels are higher in women with hyperemesis gravidarum (HG) than in unaffected pregnant controls. We postulated that higher levels of these hormones may be associated with clinically more severe HG. The aim of this study was to evaluate the effect of maternal hCG and estradiol levels on the severity of HG. Methods: A prospective study was performed on 167 first trimester women hospitalized for HG. Venous blood was taken for hCG and estradiol levels. Scattergrams were plotted for hCG or estradiol levels vs. gestational age. A curve of best fit was drawn. Women were categorized into two groups according to their position above or below the curve. Prolonged hospital stay (>= 4 days) was used as a marker for HG severity. Multivariable logistic regression analysis was used to control for differences in characteristics, laboratory results on admission, and treatment received. Results: After adjustment, high hCG level adjusted odds ratio (AOR) (2.2, 95 Cl 1.0-4.9, p=0.04) and hyponatremia AOR (2.8, 95 Cl 1.2-6.6, p=0.02) were independently associated with prolonged hospital stay. With bivariate analysis, high estradiol level was not associated with prolonged stay. Conclusions: High hCG but not estradiol is associated with more severe HG.